RANCANG BANGUN SISTEM PENJUALAN KOMPUTER BERBASIS WEB STUDI KASUS CV. KOMPUTEC BOGOR - Fuad Nur Hasan (Jurnal Akrab Juara, 2019)
The computer sales business is very profitable because now computers are no longer a luxury item but are part of the need to do work, learning and others. It can be an opportunity for CV. Komputec to expand trading reach and increase its trade online or use a website. CV. Komputec still uses a simple sales system by recording the notes and calculations using a calculator so the calculation of transactions still has weaknesses and data collection only relies on recording in the book, makes it difficult for employees to see stock, price and information. Aside from marketing products in stores, employees market their products by offering directly to agencies such as schools and offices. In this writing, an e-commerce computer sale is made to make it easier for buyers so that they do not have to bother to come to the place and employees do not need to market their products directly to agencies so they can save time and money. The research method used is the development of waterfall model software, observations, interviews and literature studies. The results of this study are the establishment of online computer buying and selling websites which can handle sales and ordering online and are able to manage buyer data.